Dominant Factors Causing Construction Project Delays in Indonesia and Their Mitigation Strategies: A Literature Review - Abd Basit Amir; Faradhiya Jinan Bastini; Andi Hasri Tri Ulandari; Muh Alfakhri Bahar (Jurnal Teknik Sipil, 2026)
Construction project delays remain a persistent issue in Indonesia, resulting in cost overruns, reduced productivity, and disruption of the intended economic benefits of projects. The increasing complexity of national infrastructure development over the past decade has further intensified challenges related to schedule control. This study aims to identify the dominant factors contributing to construction project delays in Indonesia, classify them into principal dimensions, and formulate mitigation strategies based on a synthesis of the literature. This research employs a qualitative approach using a narrative literature review method, synthesizing approximately ten key national and international studies published between 1997 and 2025. The analysis was conducted through thematic categorization to map causal factors into technical, managerial, financial, and external dimensions. The findings indicate that design changes, weak schedule control, delayed payments, as well as weather-related and regulatory factors constitute the dominant causes of project delays in Indonesia. Effective mitigation strategies include comprehensive technical planning, early-stage implementation of risk management, strengthened coordination among stakeholders, cash flow stability, and anticipation of external risks through contingency planning. The main contribution of this study lies in the development of an integrated conceptual framework linking dominant delay factors with corresponding mitigation strategies, providing a conceptual foundation for improving construction project management practices and enhancing time performance in Indonesian infrastructure projects.